Marker-Based, 3-D Adaptive Cartesian Grid Method for Multiphase Flow Around Irregular Geometries (Communications in Computational Physics, 2018)
Computational simulations of multiphase flow are challenging becausemany practical applications require adequate resolution of not only interfacial physicsassociated with moving boundaries with possible topological changes, but also aroundthree-dimensional, irregular solid geometries. In this paper, we highlight recent effortsmade in simulating multiphase fluid dynamics around complex geometries, based onan Eulerian-Lagrangian framework. The approach uses two independent but relatedgrid layouts to track the interfacial and solid boundary conditions, and is capable ofcapturing interfacial as well as multiphase dynamics. In particular, the stationaryCartesian grid with time dependent, local adaptive refinement is utilized to handlethe computation of the transport equations, while the interface shape and movementare treated by marker-based triangulated surface meshes which freely move and interact with the Cartesian grid. The markers are also used to identify the location ofsolid boundaries and enforce the no-slip condition there. Issues related to the contactline treatment, topological changes of multiphase fronts during merger or breakup ofobjects, and necessary data structures and solution techniques are also highlighted. Selected test cases including spacecraft fuel tank flow management and liquid plug flowdynamics are presented.